More, less, or the same: A scoping review of studies that compare depression between Black and White U.S. adult populations - Catherine K. Ettman; Shaffi Fazaludeen Koya; Alice Y. Fan; Grace Robbins; Joshua Shain; Yvette C. Cozier; Salma M. Abdalla; Sandro Galea (Elsevier, 2022)
The literature is divided on whether Black populations report higher or lower burden of depression than White populations in the U.S. While the life stress model might suggest that racial and ethnic minorities have greater exposure to stressors and, therefore, more depression, many studies have shown that Black populations may have less depression relative to White populations, in a phenomenon called the Black-White Depression Paradox. We aimed to assess the studies that compare depression between Black and White U.S. adults to 1) systematically document differences in depression reported between White and Black populations, and 2) assess if findings changed when studies adjusted for other variables in general and assets in particular. We conducted a scoping review of the literature from 1990 to 2020. Our final sample included 102 articles that compared depression in the U.S. for Black and White populations. We reported findings from unadjusted models and adjusted models. We further separated adjusted models by articles that adjusted for assets and articles that did not. We coded study findings as consistent with the Black-White Depression Paradox (i.e., White populations reporting depression more), Black-White Depression Disparity (i.e., Black populations reporting depression more), no significant difference, and mixed findings. Assets refer to financial (i.e., income, savings) and physical resources (i.e., homeownership). In unadjusted models (n ​= ​94), 35% of articles showed White populations reporting depression more (Paradox), 25% of studies showed Black populations reporting depression more (Disparity), 33% showed Black and White populations reporting comparable estimates of depression (No significant difference), and 7% of articles showed mixed results (Mixed). In adjusted models (n ​= ​51), the respective percentages were: 27% (Paradox), 25% (Disparity), 35% (no significant difference), and 12% (mixed). Adjusting for other variables reduced the proportion of studies consistent with the Black-White Depression Paradox and increased the proportion of studies that reported mixed findings and findings with no significant difference between Black and White populations. Among studies that adjusted for assets (n ​= ​36), the respective percentages showing the Paradox, Disparity, no difference, and mixed results were: 31%, 22%, 36%, and 11%. These findings suggest that the relation between race and depression is attributable to a range of variables that characterize the lived experience. Studies that explore the relation between race and depression among Black and White populations should be intentional about adjustment variables considered to add clarity to a complex literature.